Azure masterclass : manage Azure cloud with ARM templates (Packt Publishing, 2018)
"In the past decade, cloud computing has been gaining popularity at a tremendous rate. Some cloud providers are experiencing a growth rate of 50% year over year - which is just astounding. And the reason for this growth is obvious - cloud computing enables ubiquitous, convenient, on-demand access to a shared pool of configurable computing resources which can be rapidly provisioned and released with minimal effort. Microsoft Azure is a cloud computing platform that offers a broad set of global compute, storage, database, analytics, application, and deployment services that help organizations move faster, lower IT costs, and scale applications. The Azure Resource Manager, provided by Microsoft Azure, is a versatile service that simplifies how you manage your cloud resources. The Azure Resource Manager can help you define, build and maintain your application in a consistent manner. Within the context of Azure Stack, the Azure Resource Manager is the management layer (API) where you connect to for deploying resources. With Azure Resource Manager (ARM) you can deploy, delete, or update all resources for your solution in a single and coordinated operation by using templates. The templates are in the form of JSON format, and these templates can be used for deployment in different environments such as staging, testing, and production. The Resource Manager helps in providing auditing, security, and tagging features to help you manage your resources post-deployment. Although we have the Azure portal for managing the resources but in cases where you need to maintain and deploy multiple servers, in complex configurations - it might get a cumbersome to handle these deployment and configuration activities via the point and click portal. Moreover remembering every resource category and their respective cost evaluation can become a mammoth task. As companies look forward to automating deployment, scaling, and operations of cloud applications in the Azure cloud (across clusters of hosts), there is a need for providing automated deployment solutions for the cloud infrastructure. With Azure ARM Templates, you can define your infrastructure environment in simple JSON file template. These file templates can be versioned, validated and checked into your source control systems. This is what we call Infrastructure-as-Code (IaC)."--Resource description page